Perancangan Aplikasi Absensi Karyawan Menggunakan Geolocation dan Metode Agile Scrum Berbasis Android - Raditia Vindua; Eka Yuni Titik Artaningsih; Adam Muiz (TIN: Terapan Informatika Nusantara, 2026)
Employee attendance is an important factor in enforcing discipline, which is directly related to improving company productivity. In the digital era, companies are required to have an attendance system that is efficient, accurate, and capable of minimizing potential fraud. The manual attendance method currently used has several weaknesses, such as being vulnerable to data manipulation, difficult to verify due to the absence of accurate attendance evidence, and time-consuming in the recapitulation process. This condition becomes a challenge for construction companies engaged in infrastructure development, particularly in the gas and oil sector, because most employees work in the field. This study aims to develop an Android-based attendance system supported by geolocation technology to assist the process of recording employee attendance in real time and based on location. The system was developed using Java-based Android programming and MySQL as the database, with the Agile Scrum development method carried out gradually through planning, sprint, evaluation, and system refinement stages. The geolocation feature is used to record the latitude and longitude coordinates of employees when performing attendance, allowing attendance data to be verified by management. The testing results show that the system increased the efficiency of the attendance recapitulation process by 75%, from an average of 20 minutes manually to 5 minutes using the system. In addition, the location accuracy testing showed a coordinate suitability level of 92% based on a comparison between the attendance location points and the predetermined work locations. The black-box testing results also showed that all main system functions, including login, clock-in attendance, clock-out attendance, location validation, and data recapitulation, operated with a 100% success rate. Therefore, the Android-based attendance system with geolocation can help improve the efficiency of attendance management, reduce the potential for data manipulation, and support more effective human resource management.